Synthesis and characterization of cellulose-based nanoparticles and aerogel for biomedical application - Fiona Beragai, anak Jimmy (Universiti Malaysia Sarawak (UNIMAS), 2014)
Cellulose is the most abundant renewable material available worldwide and its non-toxic feature has propelled its popularity in pharmaceutical industries due to its biodegradability and biocompatibility. In this study, cellulose nanoparticles with mean particle sizes ranging from 70 to 360 nm were synthesized from commercial facial cotton was developed for drug delivery application. The effects of synthesis parameters such as concentration of cellulose solution, ratio of solvent/non-solvent, water-in-oil (w/o) microemulsion and surfactant on the particle size of cellulose nanoparticles formed were studied. Methylene blue (MB) as a hydrophilic model drug was loaded into cellulose nanoparticles with different mean particle sizes. In drug loading study, it was apparent that cellulose nanoparticles with the smallest mean particle size (70 nm) has the highest loading efficiency (89 %) of MB. The drug release study also unveiled that cellulose nanoparticles with the smallest mean particle size (70 nm) has the fastest release rate where 100 % of MB was released within 52 hours. Apart from being synthesized as nanoparticles, cellulose also showed a great potential as aerogels for drug delivery application. This was due to their surface properties such as its porosity and high surface area, which influence the drug loading/adsorption behavior. From this study, cellulose aerogels were successfully synthesized from cellulose fibers isolated from sugarcane bagasse (SCB) and it was apparent that cellulose aerogel with cellulose solution with the lowest concentration (1 w/v %) produced the highest BET surface area of 525 m2/g. In drug loading study, cellulose aerogel with the highest BET surface area recorded the highest loading capacity and the fastest release profile of MB, with 100 % release within 23 hours.